Identity as Pedagogy: A Work in Progress - Allison Tucker (Canadian Society for Studies in Education, 2020)
Reggio Emilia philosophy understands teaching as relationship (Malaguzzi, 1994). Høveid and Finne (2014) extend the notion of relationship as a space created between two people shaped by how we enter and engage in that space. Pedagogical relationships are influenced by how we understand our identity, which, in this study, is defined as the inner and outer forces that shape who we are (Palmer, 2017). This study will explore how identity enters teaching in profound ways; when teaching is relationship, identity is pedagogy. Residing in an ecological paradigm and theoretically situated in feminist, critical, and humanist theory, as well as the work of Dewey, I engage with a group of teachers in a narrative inquiry into teacher identity, utilizing appreciative inquiry as a structure for our conversation. Together, we seek to co-construct and illuminate how we might consider pedagogy through reflections on our evolving teacher identities and explore how identity might be seen to shape pedagogical relationships.